The Effects of Branch Spacing and Number on the Uplift Bearing Capacity of a New Squeezed Multiple-Branch Pile: A Numerical Simulation Analysis. (13th April 2023) - Su, Qingqing; Xia, Hongbing; Wu, Kunming; Yang, Fulian
Abstract : The squeezed multiple-branch pile is a variable section pile that was built by adding a bearing branch cavity to a constant section pile using expansion and extrusion equipment. It is widely used in engineering practice for its high bearing capacity, small settlement deformation, high economic benefits, strong adaptability, and simple pile forming process. In this paper, a new type of squeezed multiple-branch pile is proposed and its forming tool is invented. The forming tool of the pile has applied for an invention patent and is authorized by the China National Intellectual Property Administration. Multiple groups of comparison models of the new squeezed multiple-branch piles are established by using FLAC3D numerical simulation software to investigate the influence of the number and spacing of branches on the bearing mechanism in response to uplift load. The results indicated that the number and spacing of branches have a significant effect on the uplift bearing capacity, load–displacement curves, side friction resistance, and stress distribution law in the new pile and soil around the pile. The suitable number and spacing of branches maximize the uplift bearing capacity and minimize the settlement of a single pile.